The mystery of Pirate's Point - Panec, D. J. (We both read., 2007)
The boys' swim team has not won the annual competition against the girls' team since their mascot, a wooden parrot named Lucky, was stolen five years ago, and Sam is determined to solve the mystery and find the missing mascot.